2020
DOI: 10.4081/jphia.2020.1302
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with poor self-rated health among communitydwelling older adults in Lomé (Togo) in 2019

Abstract: The number of older adults is increasing worldwide, including in sub-Saharan Africa (SSA). However, there is a paucity of data on the overall health status of older adults living in SSA. To assess the prevalence and factors associated with poor Self-Rated Health (SRH) among community-dwelling older adults in Lomé, Togo, we conducted a cross-sectional study from January to June 2019 in Lomé among community-dwelling older adults aged 50 years and older. A 30- minute questionnaire was used to collect socio-demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Negative perceptions of the environment have been associated with poorer self-rated ( 32 ). In sub-Saharan Africa, studies on self-perception of health have been conducted, providing insights into health status among different ( 33 , 34 ). For example, a study in Togo found that self-rated health status was generally poor among older adults, particularly females, with factors such as osteoarthritis and polypharmacy being associated with poor health status ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative perceptions of the environment have been associated with poorer self-rated ( 32 ). In sub-Saharan Africa, studies on self-perception of health have been conducted, providing insights into health status among different ( 33 , 34 ). For example, a study in Togo found that self-rated health status was generally poor among older adults, particularly females, with factors such as osteoarthritis and polypharmacy being associated with poor health status ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…In sub-Saharan Africa, studies on self-perception of health have been conducted, providing insights into health status among different ( 33 , 34 ). For example, a study in Togo found that self-rated health status was generally poor among older adults, particularly females, with factors such as osteoarthritis and polypharmacy being associated with poor health status ( 33 ). In Burkina Faso, the prevalence of self-rated poor health was lower, with associations found with age, marital status, and chronic diseases ( 34 ).…”
Section: Introductionmentioning
confidence: 99%